Profiles, Proxies, and Assumptions: Decentralized, Communications-Resilient Planning, Allocation, and Scheduling - Kuter, Ugur; Kettler, Brian; Guo, Katherine; Hofmann, Martin; Champagne, Valerie; Lachevet, Kurt; Lautenschlager, Jennifer; Goldman, Robert P.; Asencios, Luis; Hamell, Josh (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
Degraded communications are expected in large-scale disaster response and military operations, which nevertheless require rapid, concerted actions by distributed decision makers, each with limited visibility into the changing situation and in charge of a limited set of resources. We describe LAPLATA, a novel architecture that addresses these challenges by separating mission planning from allocation/scheduling for scalability but at the cost of some negotiation. We describe formal algorithms that achieve near-optimal performance according to mission completion percentage and subject matter expert review: assumption-based planning and replanning, profileassisted cooperative allocation, and schedule negotiation. We validate our approach on a realistic problem specification and compare results against subject matter expert solutions.